Research on the analysis of factors affecting the deformation of the Great Wall in multimodal synergy - Z. Wang; F. Liu; Z. Zhang; X. Liu; N. Zhang; Z. Zhang; Y. Wang; Y. Tang (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2025)
This study is dedicated to the conservation of the Ming Great Wall in Beijing, and adopts a multi-integrated monitoring method aimed at monitoring and evaluating the impact of environmental vibration hazards on the deformation of the Great Wall. By coupling remote sensing technology and ground monitoring data, integrating multiple sources of data, including ground displacement monitoring system based on inertial measurement unit and global navigation satellite system, as well as synthetic aperture radar interferometry technology, we obtain high-precision vibration data and displacement information for comparison and analysis, and reveal the potential impacts of environmental factors on the Great Wall's legacy, so that we can realize continuous and dynamic monitoring and control on the Great Wall's structural stability and its surrounding environment. It also reveals the potential impacts of environmental factors on the Great Wall heritage and realizes the continuous dynamic monitoring of the Great Wall's structural stability and its surrounding environment. The results of the study show that this comprehensive monitoring method can efficiently identify and warn of vibration sources that may cause damage to the Great Wall, providing scientific basis and technical support for the protection of the Great Wall.